A 3D Moment of Fluid method for simulating complex turbulent multiphase flows. (15th February 2020) - Asuri Mukundan, Anirudh; Ménard, Thibaut; Brändle de Motta, Jorge César; Berlemont, Alain
Highlights: Numerical reconstruction of liquid/gas interface in multiphase flows based on liquid volume fraction and phase centroid. Well capture of under-resolved liquid structures. Overall second-order convergence achieved for the numerical method. MOF method and conservative momentum scheme coupling achieved. Abstract: This paper presents the moment of fluid method as a liquid/gas interface reconstruction method coupled with a mass momentum conservative approach within the context of numerical simulations of incompressible two-phase flows. This method tracks both liquid volume fraction and phase centroid for reconstructing the interface. The interface reconstruction is performed in a volume (and mass) conservative manner and accuracy of orientation of interface is ensured by minimizing the centroid distance between original and reconstructed interface. With two-phase flows, moment of fluid method is able to reconstruct interface without needing phase volume data from neighboring cells. The performance of this method is analyzed through various transport and deformation tests, and through simple two-phase flows tests that encounter changes in the interface topologies. Exhaustive mesh convergence study for the reconstruction error has been performed through various transport and deformation tests involving simple two-phase flows. It is then applied to simulate atomization of turbulent liquid diesel jet injected into a quiescent environment. The volume conservation error for the moment of fluid method remains small for this complex turbulent case.